Estimated heritability of body weight and fibers length in alpacas Huacaya - Roque Gonzalez, Juan (2019)
In this study was analyzed the body weight, fleece weight and fiber length of 1363 alpacas of the Huacayabreed, in the Sociedad Agricola de Interes Social (SAIS) Pachacutec Ltda. Nº 7, placed in Yauli county,Department of Junin, at 4200 meters over sea. The objectives were: to find averages, correlations, regressionsand heritability of body weight, fleece weight and fibers length in Huacaya alpacas. The productivecharacteristics of the 1363 alpacaswere: bodyweight, 58, 40±6, 37 kg; fleeceweight, 2, 27±0, 66 kg andfibers length, 11, 11±1, 99 cm. The weight of the progeny at birth and at weaning were: 7, 31±1, 03 and31, 41 ± 4, 96, respectively. The correlation coecients for body weight-fleece weight and fleece weight-fibers length in 1363 alpacas, have values of 0, 074 and 0, 311, respectively. The regression coecientswere 0, 009 and 1, 20 for body weight-fleece weigth and fleece weight-fibers length, respectively. To estimateheritability, records of 764 mothers alpacas (progenitor) and their ospring (progeny) was used.The calculation of the variance componentswas performed using the parent-ospring regression, the valuesof heritability of liveweight and fibers length of Huacaya alpacaswere 0, 27±0, 08 and 0, 21±0, 07,respectively.